Prognostic Impact of Blood MN1 Copy Numbers Before Allogeneic Stem Cell Transplantation in Patients With Acute Myeloid Leukemia. Issue 1 (February 2019) - Jentzsch, Madlen; Bill, Marius; Grimm, Juliane; Schulz, Julia; Beinicke, Stefanie; Häntschel, Janine; Goldmann, Karoline; Pönisch, Wolfram; Franke, Georg-Nikolaus; Vucinic, Vladan; Cross, Michael; Behre, Gerhard; et al.
Abstract : Abstract: High expression of the leukemia-associated gene meningioma-1 ( MN1 ) is frequently found at diagnosis of acute myeloid leukemia (AML) and associates with adverse outcomes. The presence of measurable residual disease (MRD) in complete remission (CR) indicates high risk of relapse and worse outcome in AML patients. However, the prognostic impact of MN1 expression levels as MRD marker has not been evaluated. Digital droplet polymerase chain reaction (ddPCR) is a novel technique allowing sensitive and specific absolute gene expression quantification. We retrospectively analyzed 124 AML patients who received allogeneic hematopoietic stem cell transplantation (HSCT) in CR or CR with incomplete peripheral recovery. Absolute MN1 copy numbers in peripheral blood were assessed prior to HSCT (median 7; range 0–29 days) using ddPCR. High pre-HSCT MN1 /Abelson murine leukemia viral oncogene homolog 1 gene ( ABL1 ) copy numbers associated with a higher cumulative incidence of relapse after HSCT and—in relapsing patients—shorter time to relapse. In multivariable analysis, high pre-HSCT MN1 / ABL1 copy numbers remained an independent prognosticator for relapse after HSCT. Patients with the highest pre-HSCT MN1 / ABL1 copy numbers also had the highest risk of relapse. MN1 copy number assessment also added prognostic information to nucleophosmin 1 gene ( NPM1 ) mutation- and brain and acute leukemia, cytoplasmic ( BAALC ) and Wilm's tumor gene 1 ( WT1 ) expression-based MRD evaluation. Our study demonstrates the feasibility of the novel ddPCR technique for MN1 / ABL1 copy number assessment as a marker for MRD. Evaluation of MN1 / ABL1 copy numbers allows the identification of patients at high risk of relapse, independently of other diagnostic risk factors and MRD markers. Abstract : Supplemental Digital Content is available in the text